Methods and concepts in geography - Chaudhuri, Manoranjan; Indian Economic Geographic Studies (Organization). (Calcutta Indian Economic Geographic Studies, 1986)
Comprises papers based on case studies from West Bengal and Maharashtra.
Keywords: Geography -- Methodology